2016
DOI: 10.1002/cbic.201500489
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum (ER)‐Targeted, Galectin‐Mediated Retrograde Transport by Using a HaloTag Carrier Protein

Abstract: Investigations into metabolic processes within the cell have often relied on genetic methods such as forced expression and knockout or knockdown techniques. An alternative approach would be introducing a molecule into the desired location inside the cell. To translocate compounds from outside cells into the endoplasmic reticulum (ER), we constructed a delivery carrier protein. This comprised N-terminal galectin-1 for cell-surface binding (G1), a protease cleavable sequence (ps), a HaloTag domain for attaching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…[4][5][6][7] A mammalian high mannose-type N-linked glycan is composed of nine mannoses with different anomeric configurations and linkage positions, and it plays an important role in the folding of glycoproteins in endoplasmic reticulum and is later reconstructed into complex N-glycans in Golgi apparatus. [8][9][10] The hybrid type of N-linked glycan is associated with infectious diseases and immunity. [11][12][13][14][15] Other forms of mannose-containing oligosaccharides i.e., glycosylphosphatidylinositol anchored glycoprotein, 16 and cell wall polysaccharides of Saccharomyces cerevisiae 17,18 and Mycobacterium smegmatis 19 also exist.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6][7] A mammalian high mannose-type N-linked glycan is composed of nine mannoses with different anomeric configurations and linkage positions, and it plays an important role in the folding of glycoproteins in endoplasmic reticulum and is later reconstructed into complex N-glycans in Golgi apparatus. [8][9][10] The hybrid type of N-linked glycan is associated with infectious diseases and immunity. [11][12][13][14][15] Other forms of mannose-containing oligosaccharides i.e., glycosylphosphatidylinositol anchored glycoprotein, 16 and cell wall polysaccharides of Saccharomyces cerevisiae 17,18 and Mycobacterium smegmatis 19 also exist.…”
Section: Introductionmentioning
confidence: 99%
“…36,38 Kanie and co-workers prepared a pseudoglycoprotein using HaloTag to analyze glycan metabolism. 37 While these reports demonstrated the recognition of glycans introduced on HaloTag by their binding proteins or enzymes, they did not investigate the role of glycans in regulating protein functions through glycan attachment. To address this gap, we introduced a fluorescent group together with the glycans to generate fluorescencelabeled pseudoglycoproteins on the cell surface, thus enabling an analysis of the protein dynamics through imaging.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Additionally, there are no restrictions on the target-glycan structures; any glycans, including oligosaccharides, can be introduced onto the POI, enabling precise structure–function-relationship studies. Pioneering studies of glycan function analysis utilizing HaloTag have been reported by Hsieh-Wilson and Kanie. Hsieh-Wilson and co-workers introduced heparan sulfate to HaloTag, reconstructing the cis interactions of the glycans with their receptors. , Kanie and co-workers prepared a pseudoglycoprotein using HaloTag to analyze glycan metabolism . While these reports demonstrated the recognition of glycans introduced on HaloTag by their binding proteins or enzymes, they did not investigate the role of glycans in regulating protein functions through glycan attachment.…”
Section: Introductionmentioning
confidence: 99%